1952
DOI: 10.1182/blood.v7.7.721.721
|View full text |Cite
|
Sign up to set email alerts
|

Some Interrelationships of Blood and the Fava Bean Principle in Vitro

Abstract: 1. Saline suspensions of human red cells, as well as those of several animal species, were agglutinated by normal saline extracts of the Fava bean. 2. This agglutination was potentiated in titer 100-fold in a medium of 10 per cent acacia, as a diluent. 3. The inhibition of the hemagglutination action of the Fava bean extract by human serum was apparently attributable to the gamma globulin fraction. 4. The Fava bean principle could be transferred from cell to cell, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1953
1953
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In one of these studies, it was observed that fungi contain hemagglutinins and hemolysins (1) and, of course, fungi are an important physiological part of the fungal-algal symbiont which comprises the lichen (15). Our observations of the inability of fresh guinea pig serum (complement) to convert the agglutinins to lysins, as well as the inhibition of lectin agglutination by normal serum, have also been reported by others (8).…”
Section: Downloaded Fromsupporting
confidence: 88%
“…In one of these studies, it was observed that fungi contain hemagglutinins and hemolysins (1) and, of course, fungi are an important physiological part of the fungal-algal symbiont which comprises the lichen (15). Our observations of the inability of fresh guinea pig serum (complement) to convert the agglutinins to lysins, as well as the inhibition of lectin agglutination by normal serum, have also been reported by others (8).…”
Section: Downloaded Fromsupporting
confidence: 88%